The acquisition of gender and declension class in a non‐transparent system: monolinguals and bilinguals. (22nd March 2013) - Rodina, Yulia; Westergaard, Marit
Abstract This article presents a corpus study of the acquisition of grammatical gender in Norwegian in two monolingual and two bilingual Norwegian‐English children. Gender in Norwegian is expressed as agreement between the noun and other targets such as determiners and adjectives, while definiteness and plurality are expressed as suffixes on the noun itself, i.e. as part of the declension. Furthermore, the gender system is characterized by relatively opaque gender assignment, suggesting that there may be a delay in the acquisition process compared to languages with more transparent systems. Our results show that, while the acquisition of suffixed forms is unproblematic, the children experience considerable problems with gender agreement. Moreover, there is generally no qualitative difference between the monolingual and bilingual children. These findings are discussed in relation to a number of issues: gender vs. declension class, the role of frequency, knowledge of the concept of gender, and monolingual vs. bilingual acquisition.